Islam and capitalism: Current Islamist modernities in Turkey (International Journal of Scientific Research and Management (IJSRM), 2017)
The main purpose of this article is to open a discussion about the contemporary interaction of capitalism and Islam in Turkey and to come up with a brand-new typology—in political/ideological, production and consumption contexts—as an outcome of this interesting interaction. The paper utilizes literature review to reach different varieties of modernity that lie at the intersection of religion and 3 mentioned contexts. Starting from the global roots of capitalistic influence on religion-related behavior, the author mainly aims to focus on the dynamics in Turkey. The article could be deemed original as it pursues to introduce a fresh classification to business, sociology and political science literatures. The findings are expected to provide readers with research ideas about production styles, cultural consumption, and political antagonism related to religion and ideology